Legal Protection For Children In Conflict With The Law (Abh) From The Perspective of Child Criminology - Fransiska Novita Eleanora; Adhalia Septia Saputri; Indah Pangestu Amritasari; Jantarda Mauli Hutagalung (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Legal protection is the authority of the government or law enforcement agencies in striving and providing a sense of security in guaranteeing legal certainty and protecting the rights of citizens from being violated, which aims to ensure that individuals can also enjoy rights in accordance with the dignity and dignity of humanity itself. While Children as Perpetrators of Criminal Acts (Juvenile Delinquency), criminology views that juvenile delinquency is often the result of the failure of the support system (family, environment, and school) or trauma. However, no matter how far the crime committed by children in conflict with the law (ABH) should not be put in prison considering that children are the next generation of the nation whose handling and placement are different and not the same as adults. Therefore, the law should not treat them like criminals or adults in order to get their rights and treat children by getting special legal protection by placing children to get restorative justice and diversion without restrictions and educational sanctions that are obtained and the implementation is supervised by law enforcement or social institutions appointed by the judge. The method implemented in this research is a normative juridical research method that refers to literature or books even from laws and regulations or analyzes from theories and principles even opinions from experts related to the research to be studied. The result is that children in conflict with the law have the right to receive legal protection in child criminology because children are still minors still need to pay attention to age limits, placement and handling of children as well as the conditions and circumstances of children without any restrictions for children who are recidivists or children who repeat criminal acts because it is based on the principle of child protection, namely the best interests of children, especially children in conflict with the law who are always considered for their rights for their future.